Reactivity of Frustrated Lewis Pair: Carbocation versus Radical Intermediates - Qu, Zheng‐Wang; Zhu, Hui; Grimme, Stefan (Chemistry : a European journal, 2024)
Recent reports of radical formation within frustrated Lewis pairs (FLPs) suggested that single‐electron transfer (SET) could play an important role in their chemistry especially for C−C coupling. In sharp contrast, our extensive dispersion‐corrected DFT calculations show that although reactive benzhydryl radical along with phosphine radical cation species can be kinetically generated from bulky phosphines and benzhydryl cation, direct P−C hetero‐coupling may lead to bulky phosphonium cation as reactive carbocation transfer reagents to styrene substrates, which is kinetically much more favorable than the recently proposed radical C−C coupling between benzhydryl radical and styrene. Similarly, meta‐stable radical cation Mes3P+⋅ salt is also kinetically accessible via SET reactions of Mes3P and B(C6F5)3 with 0.5 equivalent of p‐O2C6Cl4. Extensive DFT calculations show that both radical HCAr2⋅ and carbocation HCAr2+ are thermally accessible from the bulky phosphonium Mes3P−CHAr2+, which are further kinetically favored by HCAr2⋅ radical self‐dimerization and by nucleophilic alkene trapping, respectively.